Analisis Framing Eksploitasi Pekerja Anak di Industri Hiburan dalam Film Dokumenter The Most Beautiful Boy In The World - Hidayat, Paramitha Putri; Purwanti, Silviana; Nurliah,; Sucipta, Johantan Alfando Wikandana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to describe the media framing of the exploitation of child labor in the entertainment industry in the form of a documentary film. The research method used is the framing analysis of the Zhongdang Pan & Kosicki model with a research focus on scenes that illustrate the exploitation that occurs to Bjorn as the main character. The research results found show that Mantaray Film as a media company that produces documentary films tries to emphasize the exploitation events that have occurred are real. This can be seen from the presentation of factual events in the form of many previous archives and sources with different relationships. Other framings formed as a factor in the exploitation are Bjorn's helplessness due to loneliness and society's perception of children as fragile individuals, as well as the feminine side that envelops the ideology of masculinity as a new idea in the entertainment industry.
Keywords: Documentary Film; Child Exploitation; Entertainment Industry; Celebrity